Ultrasound-guided regional anesthesia by orthopaedic surgeons in fixation of distal radius fracture - Chun Lok Chow; Yuk Chuen Siu; Chun Man Ma; Tun Hing Lui (Journal of Orthopaedics, Trauma and Rehabilitation)
The technique of ultrasound-guided regional anesthesia has demonstrated satisfactory efficacy and safety in fixation of various fractures. There are limited studies performed concerning the applicability of a surgeon self-performed ultrasound-guided regional anesthesia. This study aimed to evaluate the efficacy of a self-performed ultrasound-guided regional anesthesia by surgeon for distal radius fracture fixation in terms of intraoperative and post-operative characteristics. Material and Methods: Patients with distal radius fracture who underwent surgery under the surgeon-performed ultrasound-guided regional anesthesia were evaluated in this retrospective study. A total of 12 patients (2 male/10 female) with a mean age of 60.6 were evaluated for the type of injury by AO classification, American Society of Anesthesiologists Classification (ASA), intraoperative visual analog scale pain (VAS) scores, duration of operation, post-operative pain control, complications and duration of hospitalisation. Result: Average age of the study population was 60.6, of which four of them were of ASA I, six of them ASA II and two of them ASA III. We provided complete pain control during the operation with all of the patient experience no pain (VAS  =  0) throughout the operation. Average operative time was 77.5 min. Average blood loss was 7.7 mL. Early post-operative pain control at 6 h after operation was well with majority of patients experience pain of VAS 1. Average post-operative hospital length of stay is 2.08 days. There was no complication arising from the application of regional anesthesia. Conclusion: Ultrasound-guided regional anesthesia can provide excellent efficacy and pain control during and after operation. Occurrence of complication was well avoided. Distal radius fracture fixation can be performed safely by orthopaedic surgeons under this technique.